Compressive split Hopkinson pressure bar testing - Chua, Dominick Chi-Yang (Nanyang Technological University, 2020)
In this era, static mechanical properties such as hardness and strength can usually be found easily from various sources online. However, most of such sources do not provide certain mechanical properties of a material such as strain rate dependant data. This information is not readily available as it was discovered that materials reacted differently in quasi-static and high strain rate conditions. Strain rate dependant data are especially important for dynamic loadings of materials within industries such as aerospace and automobile. The Split Hopkinson Pressure Bar (SHPB) also commonly known as the Kolsky Bar, is a well-known tool for high strain rate testing. The test is suitable for high strain rate testing ranging from 102 to 104 s-1. The Split Hopkinson Pressure Bar (SHPB) consist of 3 different test modes. Tension, compression, and torsion. However, this report will only be focusing and documenting the findings from the compression mode. Calibrations of the setup was done to ensure straightness in setup bars and necessary measurements were done to ensure that the specimen tolerances were met. These were factors essential to the success of the experiment. Dry run (without specimen) tests were conducted in order to obtain experimental values before the actual tests (with specimen) were conducted. A range of tests such as empty runs, calibration runs and striker bar velocity test were done with aluminium alloy, Al 6061-T6. To ensure the accuracy and validity, the obtained data will be compared with data obtained from past researches and literature.